Early Activation of Pulmonary TGF-β1/Smad2 Signaling in Mice with Acute Pancreatitis-Associated Acute Lung Injury - Hamid Akbarshahi; Asha Sam; Chaolei Chen; Ann H. Rosendahl; Roland Andersson (Mediators of Inflammation)
Acute lung injury is caused by many factors including acute pancreatitis. There is no specific therapy directed at underlying pathophysiological mechanisms for acute lung injury. Transforming growth factor-β (TGF-β) is involved in the resolution of lung injury in later phases of the disease. Some evidence exists demonstrating that TGF-β not only is involved in the late stages, but also contributes to lung injury early on in the progress of the disease. Acute pancreatitis was induced using ductal ligation in mice. TGF-β1, 2, and 3, TβRII, ALK-5, Smad2, 3, 4, and 7, and P-Smad2 expression in the lungs were analyzed at 9 and 24 h. We demonstrate that TGF-β1 levels in the lungs of mice with acute pancreatitis increase as early as 9 h after induction. We observed an increased expression of ALK-5 in acute pancreatitis at both 9 and 24 h. Inhibitory Smad7 expression was transiently increased at 9 h in acute pancreatitis, but reduced later at 24 h, with a concomitant increased nuclear translocation of phosphorylated Smad2. Our findings demonstrate activation of TGF-β signaling in the lungs as early as 24 h after acute pancreatitis, suggesting that TGF-β may represent a potential therapeutic candidate in acute pancreatitis-induced acute lung injury.